KEPEMIMPINAN GURU PAI DALAM PEMBELAJARAN DI KELAS - Nur Rima Kholifah; Fauziyah Putri; Ikhwana Desy; Suchita Martin (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This research in the form of scientific studies covers how the role of PAI teachers in providing classroom learning. This refers to the pattern of leadership that will serve as a concrete example of students. Successful educational institutions, can be seen from how the role of teachers working towards the education process takes place. So that the form of learning outcomes produce characteristics that are brought from the teacher as the educator.